Liberia : Public Investment Management Assessment. (IMF Staff Country Reports; Country Report ;, 2016)
This Technical Assistance Report presents an evaluation of the public investment management (PIM) in Liberia. The overall performance of PIM in Liberia is in line with that of comparable low-income countries, and reflects the country's post-conflict status, which severely damaged its infrastructure, and heavy dependence on external loans and grants. About 80 percent of Liberia's public investment is financed through external sources. grants and concessional loans, and executed outside the budget. These sources of funding are not within government's control and have contributed to the volatility of public investment in recent years.